Essentials of maternity, newborn, and women's health nursing - Ricci, Susan Scott (Philadelphia : Wolters Kluwer, 2021)
"This textbook is designed as a practical approach to understanding the health of women in a maternity context and the health of their newborns"--
Perspectives on maternal, newborn, and women's health care -- Family-centered community-based care -- Anatomy and physiology of the reproductive system -- Common reproductive issues -- Sexually transmitted infections -- Disorders of the breasts -- Benign disorders of the female reproductive tract -- Cancers of the female reproductive tract -- Violence and abuse -- Fetal development and genetics -- Maternal adaptation during pregnancy -- Nursing management during pregnancy -- Labor and birth process -- Nursing management during labor and birth -- Postpartum adaptations -- Nursing management during the postpartum period -- Newborn transitioning -- Nursing management of the newborn -- Nursing management of pregnancy at risk : pregnancy-related complications -- Nursing management of the pregnancy at risk : selected health conditions and vulnerable populations -- Nursing management of labor and birth at risk -- Nursing management of the postpartum woman at risk -- Nursing care of the newborn with special needs -- Nursing management of the newborn at risk : acquired and congenital newborn conditions
Includes bibliographical references and index
Keywords: Maternity nursing; Gynecologic nursing; Maternal-Child Nursing; Obstetric Nursing; Pregnancy Complications -- nursing; Pregnancy Complications